Biomonitoring of urinary di(2-ethylhexyl) phthalate metabolites of mother and child pairs in South Korea - Song, Na Rae; On, Ji-won; Lee, Jeongae; Park, Jung-Duck; Kwon, Ho-Jang; Yoon, Hae Jung; Pyo, Heesoo (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Di(2-ethylhexyl) phthalate (DEHP) is one of the common phthalate plasticizers used primarily in soft polyvinyl chloride, which is a plastic polymer that makes up the total weight of goods from 1% up to 40% in many consumer products. The aims of this study were to examine the urinary DEHP metabolites in South Korean children and to investigate the correlation between mother and child DEHP urine excretion. Three kinds of urinary DEHP metabolites: mono(2-ethylhexyl) phthalate (MEHP), mono(2-ethyl-5-hydroxyhexyl) phthalate (5-OH-MEHP) and mono(2-ethyl-5-oxohexyl) phthalate (5-oxo-MEHP), were analyzed. The total of 954 samples (n(Children) = 392, n(Mothers) = 265, n(Aadults)= 297), including 258 mother and child pairs, were analyzed using isotope dilution gas chromatography-mass spectrometry. Many studies present higher concentration of DEHP metabolites detected from adults in reproductive age than adults in other ages. Therefore, adults who are age-matched to mothers were evaluated to serve as a standard of comparison against mothers. All statistical analysis was made by adjusting detected volume concentrations (mu g/L) with respect to creatinine concentrations (mg/dL) since urinary DEHP metabolites were studied using human reference. The difference in median levels of sum of urinary DEHP metabolites was only significant when children were analyzed in relation to region (p-value <= 0.005). Among the three DEHP metabolites, only MEHP of children was significantly correlated to that of paired mothers (p-value <= 0.01). The present paper defines the relative metabolic rate (RMR) of DEHP metabolism for the first time in study on phthalates. Children had faster RMR than mothers and adults, specifically in the first step of DEHP metabolism (RMR1 MEHP hydroxylation to 5-OH-MEHP), and RMR1 of children between 1 and 24 months was the fastest. The above results may be used to study and assess human health risk from DEHP exposures, especially among mothers and children in Korea. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: GENERAL-POPULATION; PRENATAL EXPOSURE; INTERNAL EXPOSURE; RISK-ASSESSMENT; PREGNANT-WOMEN; US POPULATION; DEHP; ASSOCIATION; BIOMARKERS; GERMANY